DISPOSICIÓN FINAL DE PILAS Y BATERÍAS DE USO DOMICILIARIO EN LA LOCALIDAD DE PIRAPÓ, DEPARTAMENTO DE ITAPÚA, PARAGUAY (Journal on studies and research of academic knowledge, 2009)
The investigation looked for to analyze the aspects related to the uses and final disposition of the piles and batteries in partners’ of the Cooperative Pirapo, Department of Itapúa.  The qualitative and quantitative methodology was applied, with descriptive focus. The study universe you conformed by bosses of the partners’ of the Cooperative families, urban and rural of the town of Pirapó that you/they represent a total of 135 active partners, it was carried out a sampling at random of partners similar to 25 partners, equivalent to 18.5% with units show Those interviewed indicated to use piles and batteries in a great variety of devices for hobbies and leisure, without considering that the same ones are of well-known origin or not. The type of more consumed pile is of AA with 38%, used in remote control, clock, toys, calculators and GPS, followed by the pile D in 35% that is used in the lanterns in most of the cases.   Those interviewed use piles and batteries knowing their danger and they prepare them with scarce social responsibility, it is also related of direct form at the level of knowledge of the danger of the chemical components of these residuals, it founded that a relationship exists although very distant that is not significant according to that indicated in the obtained factorial analysis of multiple correspondences.
Keywords: piles; batteries; dangerous solid residuals